Contrasts Between Young Males Dying by Suicide, Those Dying From Other Causes and Those Still Living: Observations From the National Longitudinal Survey of Adolescent to Adult Health. Issue 3 (2nd July 2016) - Feigelman, William; Joiner, Thomas; Rosen, Zohn; Silva, Caroline; Mueller, Anna S.
Abstract : Utilizing Add Health longitudinal data, we compared 21 male suicide casualties to 10, 101 living respondents identifying suicide correlates. Method: 21 suicide decedents completed surveys in 1994/1995 (Wave 1) and 11 completed at Wave 3; responses were compared with Chi-square and oneway ANOVA tests. Results: Suicide decedents were prone to higher delinquency and fighting at Wave 1, but not at Wave 3. At Wave 1 suicide decedents remained undistinguished from living respondents in depression, self-esteem, and drug uses. Yet, after Wave 3, the 11 respondents dying by suicide showed significantly higher depression, drug use and lower self-esteem. Conclusion: Delinquency trends can readily understood, but more complex causes are needed to account for unexpected changes in self-esteem, depression and drug uses.